Physical activity and subjective well-being in old age in Indonesia - Salam, Faiz Abdu; Yuliarto, Hari; Ariestika, Elsa (UIR Press, 2021)
Old age is characterized by many problems including physical health, psychological health, and overall well-being problems. Most studies indicate a decline in subjective well-being in the geriatric population. Although many studies have investigated the relationship between physical activity and subjective well-being in old age, few have been conducted among the aging Indonesian population. This study was aimed at investigating the association between physical activity and measures of subjective well-being among older adults in Indonesia using data from a community survey. After restricting the sample to individuals aged 60 and older, a sample of 1,813 old individuals was yielded. Two models of multiple regression were estimated. In the first model, subjective well-being was predicted by physical activity. The second model added to the first model a wide range of confounding variables in order to check whether the relationship between physical activity and subjective well-being was still significant after adjusting for covariates. The main findings revealed that staying physically active was associated with high levels of life satisfaction but not with happiness beyond the contribution of gender, education, marital status, religiosity, personality, and self-rated health. Physical activity yields well-being benefits in old age and these findings are relevant for policymakers, health professionals in the geriatric field, and public health professionals.